2001
DOI: 10.1210/jcem.86.2.7212
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of 21-Hydroxylase Antibodies and Long-Term Remission of Subclinical Autoimmune Adrenalitis after Corticosteroid Therapy: Case Report

Abstract: Subclinical Addison's disease is characterized by the presence of adrenal autoantibodies (ACA) and steroid 21-hydroxylase autoantibodies (21OHAb) with or without adrenal function failure. In our previous longitudinal study some patients with high titers of ACA and at stage 2 of subclinical adrenocortical failure showed disappearance of ACA with recovery of normal adrenocortical function after corticosteroid treatment for Graves' ophthalmopathy. To investigate whether corticosteroid-induced modification of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 23 publications
0
5
0
5
Order By: Relevance
“…It is believed that Addison’s disease will only become clinically apparent if more than 90% of the adrenals are destroyed. Spontaneous remission of subclinical adrenocortical dysfunction can occur 10,11 . Clinically manifest autoimmune adrenocortical failure on the other hand is still considered to be a chronic, incurable disease leaving patients requiring lifelong glucocorticoid and mineralocorticoid replacement therapy (RT) with possible side effects of mild over‐replacement in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that Addison’s disease will only become clinically apparent if more than 90% of the adrenals are destroyed. Spontaneous remission of subclinical adrenocortical dysfunction can occur 10,11 . Clinically manifest autoimmune adrenocortical failure on the other hand is still considered to be a chronic, incurable disease leaving patients requiring lifelong glucocorticoid and mineralocorticoid replacement therapy (RT) with possible side effects of mild over‐replacement in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…However, sporadically ACA-positive patients at Stage 1-2 may improve to normal adrenal function, either spontaneously or after high doses of steroids (30). One reported patient remained in remission for more than 100 months after steroid treatment (31). In the present study, we have confirmed that the Stage 2 of adrenal cortical dysfunction at the beginning of the follow-up is an important and independent risk factor for the progression to AAD for all the patients with APS-1 or APS-2/APS-4 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Da mesma forma, a zona fasciculada pode ser protegida do ataque linfocitário por um período mais longo devido às altas concentrações de hormônios corticosteróides produzidas localmente e/ou maior habilidade de regeneração (10). Remissão dos sinais bioquímicos de disfunção adrenal pode ser observada em até 50% dos pacientes com DA potencial ou no estágio 1, associada ao desaparecimento ou negativação dos 21OHAc (62,69).…”
Section: História Natural Da Doença De Addison Auto-imuneunclassified
“…Progressos nos estudos do papel dos linfócitos T e a identificação dos auto-antígenos reconhecidos pelos seus receptores poderão levar, no futuro, ao desenvolvimento de uma vacina efetiva (10). Reversibilidade da disfunção adrenal auto-imune também pode ser induzida por corticoterapia em dose imunossupressora, apesar de títulos elevados de ACA (1:32 a 1:64), mesmo em pacientes em estágios mais avançados da insuficiência adrenocortical subclínica (69). Deve-se ressaltar que o tratamento imunossupressor da doença adrenal auto-imune ainda não está bem estabelecido, não sendo indicado, portanto, como tratamento de rotina desta doença.…”
Section: Perspectivas Futurasunclassified